2015
DOI: 10.1002/hbm.22871
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted brain network topology in pediatric posttraumatic stress disorder: A resting‐state fMRI study

Abstract: Children exposed to natural disasters are vulnerable to the development of posttraumatic stress disorder (PTSD). Recent studies of other neuropsychiatric disorders have used graph-based theoretical analysis to investigate the topological properties of the functional brain connectome. However, little is known about this connectome in pediatric PTSD. Twenty-eight pediatric PTSD patients and 26 trauma-exposed non-PTSD patients were recruited from 4,200 screened subjects after the 2008 Sichuan earthquake to underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 76 publications
(123 reference statements)
9
97
1
Order By: Relevance
“…Consistent with our study, Reuven et al reported that resting-state functional connectivity between the left SFG and DMN classical brain region increased as compared with the TEC group [31]. Furthermore, large-scale structural and functional connectivity research indicated that local parameters of the SFG in PTSD patients were higher than those in the HC and TEC groups [32,33]. Bluhm et al used resting-state fMRI to investigate childhood trauma-related PTSD.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with our study, Reuven et al reported that resting-state functional connectivity between the left SFG and DMN classical brain region increased as compared with the TEC group [31]. Furthermore, large-scale structural and functional connectivity research indicated that local parameters of the SFG in PTSD patients were higher than those in the HC and TEC groups [32,33]. Bluhm et al used resting-state fMRI to investigate childhood trauma-related PTSD.…”
Section: Discussionsupporting
confidence: 73%
“…38 We found increased clustering and path length in women with bulimia nervosa, suggesting increased local but decreased global efficiency and a shift toward regular network, which has been characterized in several other psychiatric diseases. 39,40 Although the exact mechanism remains unclear, the regularized process has been associated with reduced signal transmission speed and coordination, 41 which may be compensated by higher local efficiency to preserve efficient communication. 42 Further analysis of regional and network measures revealed both increased and decreased patterns of nodal strength and iFC in women with bulimia nervosa.…”
Section: Discussionmentioning
confidence: 99%
“…The networks differed in the number of edges (i.e., correlation matrix) (Wen et al, 2011; Shen et al, 2015). Thus, we applied a range of sparsity thresholds, defined as the fraction of the total number of edges remaining in a network, so every graph had the same number of edges (Watts and Strogatz, 1998; Wen et al, 2011; Shen et al, 2015; Suo et al, 2015). The minimum sparsity was set so that the averaged node degree of the network with threshold was 2log( N ), where N was the number of nodes, and the small-worldness scalar of the network was >1.1 (Wen et al, 2011; Shen et al, 2015; Suo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we applied a range of sparsity thresholds, defined as the fraction of the total number of edges remaining in a network, so every graph had the same number of edges (Watts and Strogatz, 1998; Wen et al, 2011; Shen et al, 2015; Suo et al, 2015). The minimum sparsity was set so that the averaged node degree of the network with threshold was 2log( N ), where N was the number of nodes, and the small-worldness scalar of the network was >1.1 (Wen et al, 2011; Shen et al, 2015; Suo et al, 2015). This thresholding strategy produced networks that could be used to estimate small-worldness with sparse properties and the minimum possible number of spurious edges (Wen et al, 2011; Shen et al, 2015; Suo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%